Seminar dan Praktek Menulis dan Membaca Teks Jawi Bagi Guru Tingkat SMP/Sederajat Sekota Sambas - Sri Sunantri; Sunandar Sunandar; Beti Yanuri Posha (Jurnal Kemitraan Masyarakat, 2024)
This article is a report on community service activities in order to fulfill the 2023 Government Assistance Program for Facilitating Cultural Advancement organized by the Region XII West Kalimantan Cultural Advancement Agency. The purpose of this article is to reintroduce, preserve and develop literacy culture, especially reading and writing in Javanese texts, to teachers, especially Islamic Religious Education Teachers (PAI) and Local Content Teachers (Mulok) at the junior high school/equivalent level in Sambas City. PAI and Mulok teachers are also the spearheads of introducing local culture. Therefore, this activity focuses on recognizing Jawi letters and reading Jawi writing. The reporting procedure is based on a qualitative descriptive approach. Data collection techniques were carried out using interviews, observation and documentation. The results of the research show that PAI and Mulok teachers at junior high school/equivalent level actively participate in seminar activities and practice reading and writing Jawi texts. This is very important because the development of an independent curriculum today requires the capacity and creativity of schools, especially teachers and is a benchmark for school progress. Apart from that, material development should focus on exploring local wisdom, one suitable material is the practice of reading and writing Javanese texts.